Hierarchically Porous Metal–Organic Frameworks: Synthetic Strategies and Applications. Issue 1 (9th January 2023) - Yao, Yao; Zhao, Xinyu; Chang, Ganggang; Yang, Xiaoyu; Chen, Banglin
Abstract : Hierarchically Porous Metal‐Organic Frameworks The development of hierarchically porous metal‐organic frameworks (HP‐MOFs) has attracted considerable interest because these materials have exceptional advantages associated with the strengths of micropores and meso‐/macropores. In article number 2200187, Banglin Chen, Xiaoyu Yang, Ganggang Chang, and co‐workers review recent advances and breakthroughs in the synthesis and applications of HP‐MOFs, emphasizing the relationships that exist between structure and applications.